Comparison between Video Podcasts and Traditional Learning in Osteoporosis for Orthopedic Resident Physicians During the COVID-19 Pandemic in Thailand - Therdyothin, Atiporn; Amphansap, Tanawat (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The coronavirus pandemic has posed challenges for medical education, including the loss of lecture hours. Resident physicians were offered video podcasts to compensate for the loss of lecture hours but without proven efficacy. This study aimed to investigate the effectiveness of video podcasts related to osteoporotic and metabolic bone diseases during residency training. Methods: Orthopedic residents were voluntarily allocated to the video podcast or traditional group. Twenty-two video podcasts covering major topics in osteoporosis and metabolic bone diseases were developed by experts and offered to the podcast group. Each podcast was approximately 20-30 minutes long. Pre- and post-exposure examinations, comprising 60 multiple-choice questions, were conducted and compared. Confidence, perceived ability, and preferences were assessed using questionnaires. Results: A total of 37 residents were recruited, 18 in the video group and 19 in the traditional group. With numerically lower pre-test scores (47.59%±9.77% in the video group, 53.95%±9.77% in the traditional group, p = 0.056), students in the video group significantly outperformed the traditional group in the post-test (89.81%±3.83% and 76.93%±10.92%, p < 0.001). Junior residents watching videos scored higher than senior residents. Videos led to a greater gain in confidence and perceived ability. However, students still preferred live lectures to videos. Conclusions: This study showed greater performance scores and confidence when using video podcasts, with junior residents improving more with podcasts. We suggest providing supplemental video podcasts in non-surgical-based subspecialties during the early training years as a supplement during the pandemic and a new normal residency training method.